2006
DOI: 10.1159/000098226
|View full text |Cite
|
Sign up to set email alerts
|

Rice: Another Potential Cause of Food Allergy in Patients Sensitized to Lipid Transfer Protein

Abstract: Recent studies show that the lipid transfer protein (LTP), the major Rosaceae allergen in patients not sensitized to birch pollen, is a largely cross-reacting allergen. Moreover, it is a potentially hazardous allergen due to its stability upon thermal treatment and pepsin digestion. The present study reports 3 cases of rice-induced anaphylaxis in LTP-allergic patients. In vitro inhibition studies, carried out using LTP purified from both rice and apple as well as whole peach extract, show that LTP was the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Cross-reactivity between Pru p 3 and food nsLTPs from taxonomically distantly related plant species was assessed in previous studies either by using extracts containing unknown amounts of nsLTP and/or mainly in a semi-quantitative manner by immunoblotting inhibition experiments [20,21,24,26,27,28]. In the present study, experimental conditions were clearly defined, as purified and structurally characterized allergen molecules were used in dose-dependent assays, allowing a quantitative evaluation of data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-reactivity between Pru p 3 and food nsLTPs from taxonomically distantly related plant species was assessed in previous studies either by using extracts containing unknown amounts of nsLTP and/or mainly in a semi-quantitative manner by immunoblotting inhibition experiments [20,21,24,26,27,28]. In the present study, experimental conditions were clearly defined, as purified and structurally characterized allergen molecules were used in dose-dependent assays, allowing a quantitative evaluation of data.…”
Section: Discussionmentioning
confidence: 99%
“…cherry [4], apricot [4,17], plum [4,18], pear [1], apple [1,19] and strawberry [1,20], and non-Rosaceae foods, i.e. walnut [14,21], peanut [14], hazelnut [22], orange [23], cabbage [24], wheat [25], rice [26] and grape [27,28]. Pre-incubation of patient sera with Pru p 3 or peach extract was capable of abolishing IgE binding to almost all homologous allergens, an observation underlining the strong cross-reactivity of IgE directed against Pru p 3.…”
Section: Introductionmentioning
confidence: 99%
“…These foods were chosen because they have been reported to cause potentially severe allergic reactions in LTP-hypersensitive subjects [16,17,18,19,20,21]. Reported symptoms were classified as local (oral allergy syndrome, OAS) or systemic (urticaria or anaphylaxis).…”
Section: Methodsmentioning
confidence: 99%
“…Other known rice allergens in rice grains include a novel type of plant glycoxalase I of 33 kDa and an α-globulin of 26-28 kDa [14,15,16]. Moreover, two studies identified a lipid transfer protein (LTP) as a potential allergen involved in symptoms induced by ingestion of cooked rice or inhalation of raw rice in patients who are allergic to Prunoideae fruits [7,17]. Trcka et al [18] identified a 56-KDa protein as a relevant allergen in patients with rice-induced anaphylaxis.…”
Section: Introductionmentioning
confidence: 99%